A Serum Metabolic Profiling Analysis During the Formation of Fatty Liver in Landes Geese via GC-TOF/MS - Gong, Yujie; Lyu, Wentao; Shi, Xingfen; Zou, Xiaoting; Lu, Lizhi; Yang, Hua; Xiao, Yingping (Frontiers in Physiology, 2020)
During the process of fatty liver production by overfeeding, the levels of endogenous metabolites in the serum of geese would change dramatically. This study investigated the effects of overfeeding on serum metabolism of Landes geese and the underlying mechanisms using a metabolomics approach. Sixty Landes geese of the same age were randomly divided into the following 3 groups: D0 group (free from gavage); D7 group (overfeeding for 7 days); D25 group (overfeeding for 25 days). The results showed that overfeeding significantly increased the body weight and the liver weight of geese. Serum enzymatic activities and serum lipid levels were significantly enhanced following overfeeding. Gas chromatography time-of-flight/mass spectrometry (GC-TOF/MS) was employed to explore the serum metabolic patterns, and to identify potential contributors to the formation of fatty liver and the correlated metabolic pathways. A large number of endogenous molecules in serum were altered, especially at the late stage of overfeeding (7 days to 25 days). Continuous elevated levels of pyruvic acid, alanine, proline and beta-glycerophosphoric acid and reduced lactic acid level were observed in the serum of overfed geese. Pathway exploration found that the most of significantly different metabolites were involved in various amino acids metabolism, carbohydrate metabolism and lipid metabolism. These findings pinpoint specific metabolite changes and identify potential biomarkers for early diagnosis of fatty liver disease, as well as provide insights into the perturbation of metabolic pathways involved in fatty liver formation.